Reflections on Schooling and Work in the Life of Brazilian Girls and Women from the Short Life Maria (Research, Society and Development, 2019)
This study uses the short film Vida Maria (Ramos & Ramos, 2006) as an important opportunity to deepen the discussion about schooling, work and gender in the life histories of girls and women. This study makes the reflection about the film in the perspective of education always denied and therefore of the ever renewed conditions of life and subordinate work, we seek to establish the counterpoint with the reality of women students of technical courses who had experiences similar to those of Mary José in his childhood and who, somehow, seek to overcome this vicious circle of misery and submission, among other factors, due to access to vocational training. As a research modality we opted for an exploratory and qualitative study conducted at a federal technical school with students of the technical course in administration. Empirical data were collected through a focus group. The experience lived by the students was analyzed looking for the convergences, divergences and or idiosyncrasies of the approximation between science and art through the short film "Vida Maria" in dialogue with literature. The results point out that the story of "Mary" is far from just a fiction, they depict the truth, the reality lived by these women these days.